The oncoprotein Myc controls the phosphorylation of S6 kinase and AKT through protein phosphatase 2A. Issue 12 (21st August 2018) - Chellini, Lidia; Monteleone, Valentina; Lombari, Malinska; Caldarola, Sara; Loreni, Fabrizio
Abstract: This study focuses on the effects of Myc oncoprotein on the translational apparatus of the cell. Translation is an energy consuming process that involves a large number of accessory factors. The production of components of the protein synthesis machinery can be regulated at the transcriptional level by specific factors. It has been shown that the product of the oncogene Myc, a transcription factor frequently activated in cancer, can control translational activity through an increase in the transcription of the eIF4F complex components (eIF4E, eIF4AI, and eIF4GI). However, additional effects at the posttranslational level have also been described. For instance, it has been shown that Myc upregulation can induce mammalian target of rapamycin (mTOR)–dependent 4E‐binding protein 1 (4E‐BP1) hyperphosphorylation. We induced overexpression or inhibition of Myc through transfection of complementary DNA constructs or specific small interfering RNA in PC3 (prostate carcinoma) and HeLa (cervical carcinoma) cells. We have observed that overexpression of Myc causes an increase in 4E‐BP1 phosphorylation and activation of protein synthesis. Unexpectedly, we detected a parallel decrease in the phosphorylation level of S6 kinase (in PC3 and HeLa) and AKT (in HeLa). We report evidence that these changes are mediated by an increase in protein phosphatase 2A activity. Abstract : The phosphorylation of mechanistic target of rapamycin targets is differentially affected by Myc overexpression. Activity of protein phosphatase 2A is the cause of hypophosphorylation of S6K and AKT. Myc overexpression induces an increase of methylated protein phosphatase 2A catalytic subunit.